143 Metastatic Renal Cell Carcinoma to the Head and Neck Area: A Clinicopathologic Study. (11th January 2018) - Mir, Fatima; Alnajar, Hussein; Rupcich, Christine; Reddy, Vijaya; Gattuso, Paolo
Abstract: Objectives: Renal cell carcinoma (RCC) accounts for approximately 3% of all adult malignancies. Common metastatic sites include lung, bone, and liver. However, head and neck region metastases from a renal cell carcinoma are an uncommon clinical manifestation. We performed a retrospective review to assess the incidence of metastatic renal cell carcinoma in the head and neck region and sites of involvement. Methods: Our surgical pathology files from 1990 to 2015 were searched to identify cases of metastatic RCC in the head and neck region. Pertinent clinicopathologic data were reviewed. Results: A total of 565 RCC cases were identified. Fifteen of 565 (2.6%) had metastatic RCC to the head and neck region. Of these 15 patients, there were 10 men and five women. The median age at diagnosis was 63 years, ranging from 37 to 76 years. The most common sites of metastases were thyroid and scalp with sinuses, skull, lymph node, and maxilla involved in decreasing order of frequency. Two of 15 (13.3%) cases presented with distant (head and neck) metastases at the time of diagnosis. The median time of diagnosis of metastasis for 12/15(80%) cases was 73 months. Twelve of 15 cases had predominantly "clear cell" morphology in the metastatic lesion. Conclusion: Our study illustrates a variety of extracranial metastatic sites in the head and neck affected by RCC. Since the majority of metastatic tumors had clear cell morphology, it may be difficult to differentiate a primary clear cell tumor of the salivary glands or thyroid gland vs a metastatic RCC, especially in patients with an occult primary RCC. Patients with RCC are well known to have late metastases during their course of disease. Mean time of metastasis in our study was 73 months.